Fatty Acid and Lipid Transport in Plant Cells. (February 2016) - Li, Nannan; Xu, Changcheng; Li-Beisson, Yonghua; Philippar, Katrin
Abstract : Fatty acids (FAs) and lipids are essential — not only as membrane constituents but also for growth and development. In plants and algae, FAs are synthesized in plastids and to a large extent transported to the endoplasmic reticulum for modification and lipid assembly. Subsequently, lipophilic compounds are distributed within the cell, and thus are transported across most membrane systems. Membrane-intrinsic transporters and proteins for cellular FA/lipid transfer therefore represent key components for delivery and dissemination. In addition to highlighting their role in lipid homeostasis and plant performance, different transport mechanisms for land plants and green algae – in the model systems Arabidopsis thaliana, Chlamydomonas reinhardtii – are compared, thereby providing a current perspective on protein-mediated FA and lipid trafficking in photosynthetic cells. Trends: FAX1, a novel membrane protein in the inner envelope of chloroplasts, mediates FA export. The discovery and analysis of membrane transporters allows future development of models for transport mechanisms of lipophilic compounds. The flow of FAs from plastids to their final cellular destination in lipid molecules is controlled by membrane-intrinsic and membrane-attached proteins. Plant membrane transporters for FAs and lipid derivatives represent essential components in growth, development, and plant performance.